A study of correlation of degree of midline shift on computed tomography scan and Glasgow coma scale in patients of acute traumatic head injury - Chaurasia, A. K.; Dhurve, Lalit; Gour, Rajneesh; Kori, Rajpal; Ahmad, Avias K. (International Surgery Journal, 2021)
Background: Traumatic brain injury is one of most common cause of death in road traffic accident. Most of these classified as mild injury, with approximately 20% classified as moderate to severe. Approximate 50% of the 150,000 trauma deaths every year are caused by head injury. Methods: A prospective cross-sectional study was conducted on 150 patients with a head injury admitted in the Hamidia hospital, Bhopal. The assessment of the severity of head injury using Glasgow coma scale (GCS) at the time of admission, follow up on 5 days and 15 days respectively. The collected data were transformed into variables, coded and entered in Microsoft excel. Data were analyzed and statistically evaluated using statistical package for the social sciences (SPSS)-PC-21 version. Results: Out of 150, a total of 115 patients had no midline shift while 35 patients were having midline shift. Severe head injury patients (GCS 3-8) were having more morbidity and mortality. Moderate head injury (GCS 9-13) was associated with good prognosis and low mortality. A greater degree of midline shift of (more than 5 mm) is indicated severe head injury and is significantly associated with morbid outcome and higher mortality. Conclusions: In our study, road traffic accidents is the most common cause of head injury, with males being affected more than females. The degree of midline shift on computed tomography (CT) scan head in patients with head injuries was found to be significantly associated with high mortality and morbidity.